ARAH KEBIJAKAN PEMANFAATAN DAN PENYALURAN DANA PENDIDIKAN PADA ERA OTONOMI DAERAH - Suwandi Suwandi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe purposes of this article are to reveal (1) the policy direction for the allocation and utilization of the education funding, and (2) the distribution model of the education budget from the goverenment to the schools in this local autonomy era. This research is based on literature study. The analysis results showed that (1) the policy direction for the allocation and utilization of education funding still need to be improved in case of its quantity to fulfill the mandate of Law No.20 Year 2003, i.e. 20% from State Budget (APBN) and Local Budget (APBD) excluding salaries and specific-administrative school, (2) Generally, the distribution model of education funding from the central government in the forms of block grant, deconcentration (including BOS/BKM) and from the Ministry of Religious Affairs, Provincial Budgets and Local Budget were still feasible for the distribution of education funds to schools with several improvements, especially for the empowerment of the Provincial Education Department and the Education Department of City/ district to participate as an advisor and controller of the implementation of school programs. Keywords : education fund, local autonomy, block grants, deconcentration